Implementation of the Family Learning Center (PUSPAGA) Program in Preventing Violence Against Women and Children in Surabaya City - Fenita Arisqi Putri; Indah Prabawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The implementation of the Family Learning Center (Puspaga) Program is inseparable from the implementation of policies supervised by the Surabaya City Department of Women's Empowerment and Child Protection as well as Population Control and Family Planning (DP3APPKB). However, in its implementation there are obstacles namely the lack of public awareness regarding family problems that are still low to be submitted and the program socialization is not optimal. Therefore, this study aims to define the family learning center program or Puspaga implemented in Surabaya City. The type of research used is descriptive qualitative, which is analyzed with several policy indicators according to the opinion of Van Meter and Van Horn which includes policy standards and targets, resources, characteristics of implementing agents, communication between organizations, attitudes of policy implementers, economic, social, and political environments. The research subjects involved were the DP3APPKB of Surabaya City, Puspaga Kota, and additional data were obtained from residents of Surabaya City. This research was conducted at DP3APPKB and Puspaga Siola of Surabaya City using observation, interview, and documentation methods. The data collection techniques used in this study were data analysis, data presentation, and drawing conclusions based on primary and secondary data. The results of this research explain that communication between DP3APPKB and policy implementers and the community in delivering the program is clear, but there is a lack of knowledge of Puspaga human resources and a lack of awareness and enthusiasm from the community who are willing to use Puspaga services in Surabaya City.